ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL KEMEMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Desi Irawati; Gida Kadarisma (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
The purpose of this study was to analyze the difficulties of students in solving problems of mathematical problem solving abilities of students of SMP Negeri in West Bandung Regency. The method used in this research is descriptive method. The subjects of the study were 26 people of SMP Negeri 1 Rongga class VII-C. The instrument used includes a test instrument of mathematical problem solving ability of triangular and rectangular material, as many as 5 questions containing four problem solving indicators, namely understanding the problem, planning the solution strategy, solving the problem according to the plan, and checking the answers again. Obtaining the results of the answers is done by giving a score for each indicator. Percentage of each indicator is obtained by finding the average student's answer. The results of this study were the lowest percentage of problem solving ability indicators found in the indicator of checking the truth and the average problem-solving ability obtained was in the moderate category.